2022
DOI: 10.3389/fnins.2022.834058
|View full text |Cite|
|
Sign up to set email alerts
|

Virus-Induced Maternal Immune Activation as an Environmental Factor in the Etiology of Autism and Schizophrenia

Abstract: Maternal immune activation (MIA) is mediated by activation of inflammatory pathways resulting in increased levels of cytokines and chemokines that cross the placental and blood-brain barriers altering fetal neural development. Maternal viral infection is one of the most well-known causes for immune activation in pregnant women. MIA and immune abnormalities are key players in the etiology of developmental conditions such as autism, schizophrenia, ADHD, and depression. Experimental evidence implicating MIA in wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 105 publications
0
43
0
2
Order By: Relevance
“…Thus, it is not the pathogen that serves as a teratogen, but the activation of the maternal immune system 25 . Viral pathogens—including non‐vertically transmitted influenza viruses—are still the leading environmental cause of MIA 26 …”
Section: Maternal Immune Activation During Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is not the pathogen that serves as a teratogen, but the activation of the maternal immune system 25 . Viral pathogens—including non‐vertically transmitted influenza viruses—are still the leading environmental cause of MIA 26 …”
Section: Maternal Immune Activation During Pregnancymentioning
confidence: 99%
“…25 Viral pathogensincluding non-vertically transmitted influenza viruses-are still the leading environmental cause of MIA. 26 Historical outbreaks of influenza infection, dating back almost a century, provide population-based epidemiologic data that support the connection between maternal infection and offspring NDDs. 4,8 To this day, influenza viruses are considered prototypical re-emerging global pathogens, as they are stably adapted to and transmitted within multiple host species.…”
mentioning
confidence: 99%
“…Neuroimaging evidence of volume loss in the central nervous system (CNS) and microglial activation provides additional support for the importance of a low-level neuroinflammatory process in SCZ ( 56 ). The early twentieth century-famous infectious theory of psychosis ( 58 ) has now gained additional scientific justification ( 59 62 ). It has been shown that SCZ is a multifactorial disease that results from the interaction of SCZ susceptibility genes with environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…The data collected from the offspring of gestational parents who were admitted to hospital due to infection suggest an ASD hazard ratio of 2.98 (95% CI 1.24-7.15) due to viral infection in the first trimester and 1.42 (95% CI 1.08–1.87) for bacterial infection in the second trimester (5). Especially with a large number of Covid-19 cases in pregnant people in the last years, it will be important to consider possible effects of maternal Covid-19 infection on the offspring in the near future (7). Common to different types of infection is the increase in cytokines and chemokines that, either via placental transfer or induction of placental inflammation and subsequent cytokine and chemokine release, leads to elevated concentrations of these immune mediators in the fetal compartment with consequences for the developing brain (7).…”
Section: Introductionmentioning
confidence: 99%
“…Especially with a large number of Covid-19 cases in pregnant people in the last years, it will be important to consider possible effects of maternal Covid-19 infection on the offspring in the near future (7). Common to different types of infection is the increase in cytokines and chemokines that, either via placental transfer or induction of placental inflammation and subsequent cytokine and chemokine release, leads to elevated concentrations of these immune mediators in the fetal compartment with consequences for the developing brain (7). Elevated concentrations of the pro-inflammatory cytokine interleukin-6 (IL-6) during pregnancy have been associated with newborn offspring brain anatomy as well as structural and functional connectivity with consequences for cognitive function in infancy (810).…”
Section: Introductionmentioning
confidence: 99%